Associations Between Diabetic Retinal Microvasculopathy and Neuronal Degeneration Assessed by Swept-Source OCT and OCT Angiography - Qiu, Bingjie; Zhao, Lin; Zhang, Xinyuan; Wang, Yanhong; Wang, Qiyun; Nie, Yao; Chen, Xiaosi; Cheung, Carol Y. L. (Frontiers in Medicine, 2021)
Purpose: To provide clinical evidence of the associations between retinal neuronal degeneration and microvasculopathy in diabetic retinopathy (DR). Methods: This cross-sectional study included 76 patients (76 eyes) with type 2 diabetes mellitus (DM), refraction error between -3.0 and +3.0 D. The eyes were assigned into DM (without DR), non-proliferative DR (NPDR), and proliferative DR (PDR) groups. Age-, sex-, and refractive error-matched normal subjects were enrolled as controls. The mean retinal thickness (mRT), the relative mean thickness of the retinal nerve fiber layer (rmtRNFL, mtRNFL/mRT), ganglion cell layer (rmtGCL), ganglion cell complex (rmtGCC) layer, the foveal avascular zone area (FAZa), FAZ perimeter (FAZp), FAZ circularity index (FAZ-CI) and the vessel density (VD) in superficial capillary plexus (SCP) and deep capillary plexus (DCP) were assessed by swept-source optical coherence tomography (OCT) and OCT angiography. Group comparison and Spearman partial correlation coefficient analysis were applied to evaluate the correlation between these morphological parameters. Results: The FAZa and FAZp in SCP and DCP increased with the DR severity (PFAZa, SCP=0.001; PFAZa, DCP=0.005; PFAZp, SCP<0.001; PFAZp, DCP<0.001). The rmtGCL, FAZ-CI in SCP and DCP, VD in DCP decreased with the DR severity (PrmtGCL=0.002, PFAZ-CI, SCP=0.002; PFAZ-CI, DCP<0.001 PDCP<0.001). After controlling the age, sex, duration of diabetes and hypertension, the rmtRNFL, FAZa in SCP and DCP, FAZp in SCP and DCP were correlated with the severity of DR (P<0.05), while VD in SCP and DCP, FAZ-CI and rmtGCL were negatively correlated with the severity of DR (P<0.05). The rmtGCL was negatively correlated with the FAZa in SCP (r = -0.339, P =0.002) and DCP (r = -0.234, P =0.033), FAZp in SCP (r = -0.369, P =0.001) and DCP (r = -0.317, P =0.003), but positively correlated with VD in SCP (r = 0.263, P =0.016), VD in DCP (r = 0.276, P =0.012), and FAZ-CI in DCP (r = 0.307, P =0.006). Conclusions: rmtRNFL, FAZ-CI in SCP and DCP, FAZp in SCP are strong predictors of the severity of DR. The ganglion cell body loss is highly correlated with increased FAZp and FAZa, decreased FAZ-CI and reduced VD with the severity of DR.